Modeling and Analysis of Dynamic Social Ties in D2D Collaborative Video Transmission - Qi Zhang; Zufan Zhang; Tian Zeng; Xiaoke Li (Discrete Dynamics in Nature and Society)
Social networks are one of the main carriers of information diffusion. Changes in social ties will affect the quality of Device-to-Device (D2D) communications especially the video transmission. For further improving the communication utility of users, it is of great significance to effectively integrate D2D communications and social networks. To this end, this paper utilizes a stochastic approach to modeling and analysis of dynamic social ties in D2D collaborative video transmission. Specifically, a stochastic mathematical model is established and analyzed, in which the combined effect of many factors such as interest, geographical position, career, social class, value system, and interaction is considered. Based on the Brownian motion theory, the strength of social ties among social individuals with time is studied. Next, the reliability function and adaptive parameter estimation are performed. Finally, some examples are conducted to illustrate the main results of this paper, from which one can see that the proposed model has a good predictive ability of the changing trend of social ties.